Best Proximity Point Theorems for G, D-Proximal Geraghty Maps in JS-Metric Spaces. (1st December 2020) - Charoensawan, Phakdi; Chaobankoh, Tanadon
Abstract : We study G, D -proximal Geraghty contractions in a J S -metric space X endowed with graph G . We obtain some best proximity theorems for such contractions. An example and several consequences are given. As a consequence of our results, we also provide the best proximity point results in X endowed with a binary relation.